1993
DOI: 10.2307/3496014
|View full text |Cite
|
Sign up to set email alerts
|

Ant Behavior and Microbial Pathogens (Hymenoptera: Formicidae)

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.. Florida Entomological Society is collaborating with JSTOR to digitize, preserve and extend access to The Florida Entomologist.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
82
0
1

Year Published

2001
2001
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(86 citation statements)
references
References 29 publications
3
82
0
1
Order By: Relevance
“…Social insects use diverse methods to prevent and combat disease agents, such as grooming or other hygienic behaviours and the use of antimicrobial compounds from glandular secretions or external sources (e.g. bacteria; Oi & Pereira 1993;Currie et al 1999a;Mueller et al 2005). The evolution of larger colony sizes places greater demands on 'public health' adaptations (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Social insects use diverse methods to prevent and combat disease agents, such as grooming or other hygienic behaviours and the use of antimicrobial compounds from glandular secretions or external sources (e.g. bacteria; Oi & Pereira 1993;Currie et al 1999a;Mueller et al 2005). The evolution of larger colony sizes places greater demands on 'public health' adaptations (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Previous work has shown that different ant-fungal interactions can influence the behaviour of hosts in several ways (e.g., increased grooming and nest cleaning, secretion of antibiotics, pathogen avoidance, dispersal of infected individuals, and the relocation of an entire colony) (e.g., Csata et al 2014, Roy et al 2006, Oi and Pereira 1993. Laboulbeniales fungi are often present on the ant body with high thallus densities and the results of recent studies suggest that they could have both positive and negative effects on their hosts and are able to influence their behaviour (Báthori et al 2015a, Csata et al 2014, Konrad et al 2015, Pech and Heneberg 2015.…”
Section: Introductionmentioning
confidence: 99%
“…Ants and other social insects perform trophallaxis and allogrooming to transfer food among nestmates (Wheeler, 1918;Wilson, 1971;Hölldobler and Wilson, 1999), eliminate pathogens and parasites for colonial sanitation (Oi and Pereira, 1993;Currie et al, 1999;Fernández-Marín et al, 2009) and exchange cuticular hydrocarbons (CHCs) to maintain nestmate recognition (Hölldobler and Wilson, 1999;Greene, 2010;Liebig, 2010;Van Zweden and d'Ettore, 2010). Nestmate recognition is a cognitive process whereby a worker accepts or rejects the encountered conspecifics after detecting CHCs on the body surface by antennal sensory organs (Ozaki et al, 2005;Ozaki and Wada-Katsumata, 2010).…”
Section: Introductionmentioning
confidence: 99%